Cost Reduction Of Hand Mixer Using Design For Manufacture And Assembly (DFMA) - Wan Ismail, Wan Muhammad Safwan; Nawawi, Azli (Progress in Engineering Application and Technology, 2021)
As the competition of a product at the market is tight, a product must have the best performance with an affordable price. A product needs to be improved to keep competing globally thus the application of Design for Manufacture and Assembly (DFMA) is the best choices in designing the new and better version of a product. This thesis has emphasized the advantages of application of DFMA methodology to a product. DFMA methodology as basically to simplified the design and cost reduction to the original design. The methodology of the study was using the manual DFA calculation method on the chosen product, hand mixer. The manual Design for Assembly (DFA) methodology was conducted as the DFMA application to the hand mixer was explained. The method of the study been conducted was explained and the evaluation of the design efficiency through the manual DFA analysis can also be explained. The original design of the hand mixer with operation time per unit, 282.43s and operation cost per second was RM0.4903. Meanwhile, the improved design hand mixer efficiency was 57.01%, reducing the cost and operation time with RM0.4019 per second and 231.53s respectively. The design efficiency of the original design hand mixer was of 46.7%. The improvement of 22.08% design efficiency was produced from the improved design hand mixer. Using the manual DFA methodology, the efficiency design performance comparison between the original design and the improved design was conducted and the improvement was able to be made.